Self Care Behaviours, Quality of Life Among Patients with Heart Failure - F. Shojaei; M. Asemi; A. Najaf Yarandi; F. Hosseini (Iran University of Medical Sciences, 2006)
As a matter of the fact, patient with a disability and chronic diseases such as heart failure, suffer from many health related problems. Promoting health and quality of life of these patients will be feasible, if they could promote their self care behaviours. In order to assess self care behaviours of these patient and its relationship with quality of life, we conducted a correlationel descriptive study which 250 participants selected by random sampling, and a questionnaire used as a data gathering instruments.  The study findings showed that a statistically significant relationship was existed between self care behaviours and the quality of life (P=0.00). We also found that 76.4% of the participants possessed undesirable and less desirable levels of quality of life. 74% of the patients had moderate and low scores of self care behaviours to sum up the results, the study findings showed that the majority of the sample group had unsatisfactory self care behaviours and quality of life scores. Therefore, systematic self care educational programs are of great need to be held by nurses,whom had been trained and academically educated for this goal.